Estudio de criptomonedas como alternativa de inversión en la ciudad de Loja - Torres Yaguana, Fernando Joao (2024)
Cryptocurrencies have emerged as an increasingly popular investment alternative in the financial world. Unlike traditional investments, these decentralized digital currencies offer unique opportunities to diversify and expand investment portfolios. Through blockchain technology as a basis, cryptocurrencies allow secure and transparent transactions, without intermediaries. Therefore, their high volatility and potential for significant returns attract investors looking for growth opportunities. The general objective is to analyze cryptocurrencies as an investment alternative in the city of Loja, which is why we studied people in the city who have made some type of traditional investment and, on the other hand, people who have invested in cryptocurrencies, in order to determine the profitability of both groups and establishing the respective comparison through econometric calculations. In addition, a mixed approach was used to analyze historical data on returns, as well as surveys to understand perceptions and attitudes towards cryptocurrencies in Loja. Based on this, the results demonstrated the growing adoption of cryptocurrencies in the city and a trend towards their use as an investment instrument. The study provided valuable information for investors interested in diversifying their portfolios and for the development of financial policies in the region. It was concluded that while cryptocurrencies offer investment opportunities, a sound understanding of the risks and an appropriate portfolio management strategy is essential to maximize potential returns.